Dietary polyphenols maintain human health through modulation of gut microbiota - Rudrapal, Mithun; de Oliveira, André M.; Singh, Ravi Pratap (Frontiers in Pharmacology, 2026)
The symbiotic interplay between dietary polyphenols and gut microbiota constitutes a focal point in contemporary scientific investigations, with profound impact in human health and diseases. The human gastrointestinal milieu serves as the locus for a diverse consortium of microbial organisms, collectively constituting the gut microbiota, which intricately modulate host metabolism, immune responses, and overall homeostasis. Dysregulation of gut microbial composition and functionality, known as dysbiosis, has been implicated in the progression of a plethora of gastrointestinal and systemic maladies, encompassing inflammatory bowel diseases, metabolic syndromes and neurological disorders, and so on. Polyphenols abundant in plant-derived food, exert multifaceted biological activities, encompassing antioxidative, anti-inflammatory and anticancer properties, among many others. These polyphenolic metabolites inextricably interact with the gut microbiota, exerting modulatory effects on microbial composition and functionality, thereby promoting the symbiotic physiological relationships between microbe and human host. In reciprocal fashion, the gut microbiota serves as pivotal vectors in the metabolism and bioavailability of polyphenols, engendering bioactive signalling metabolites which regulate systemic physiological effects and thereby maintain host health. This review emphasizes the imperative of comprehensively delineating an interplay between polyphenolic metabolites and gut microbiota in maintaining host health, while reflecting potential interventions of protective health outcomes in disease conditions.